Analysis of Pediatric Rasmussen Encephalitis: Experience from A Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Child Health, 2022)
Background: Rasmussens encephalitis (RE) is rare progressive cerebral inflammatory disease predominantly affecting pediatric population. The key clinical features are seizure and hemiparesis. Seizure is mostly focal with or without epileptia partialis continua (EPC). Diagnosis is established by EEG showing epileptic discharges with focal slowing, focal cortical atrophy in neuroimaging and T cell dominated encephalitis in biopsy or autopsy. This study was done to describe the clinical, laboratory features and treatment of RE in Bangladesh perspective.Materials & Methods: This study was done in Department of Pediatric Neurology, IPNA, BSMMU, Dhaka, Bangladesh. Four admitted children who were diagnosed as RE from January 2016 to July 2019 were included in this study. Retrospective detail data of the all four patients were collected and analyzed.Results: The age ranging was 3-12 years, all were male. Cognitive decline, speech disorder, hemiparesis were observed in all the patients. Among them 1 had prodrome of fever. All the patients had seizure, mostly focal onset. Among them 2 had EPC. Treatment was given mainly with immune modulatory drugs (Intravenous methyl prednisolone, IV immunoglobulin, oral steroids) and antiepileptic drugs. On follow up all the patients had consequences in the form of hemiparesis, epilepsy, dysphasia, cognitive disorder etc.Conclusion: Cognitive decline, speech disorder, focal seizure and hemiparesis were the common presentation. EPC was observed in 50% of cases and consequences on follow up in all cases.BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 147-154